Analisis Biaya Manfaat Program Jaring Pengaman Sosial di Kabupaten Labuhan Batu - Esti Pancaningdyah (Magister Administrasi Publik, 2000)
This research is aimed at evaluating the program namely Local People Empowerment for Overcoming Economic Crisis Impact (Pemberdayaan Daerah dalam Mengatasi Dampak Krisis Ekonomi â€“ PDM-DKE) which relates to the social safety net program in six villages of Labuhanbatu Regency. Two basic cast-benefit analysis are used â€” the Net Benefit (NB) and the Cost-Benefit Ratio (CBR) — to evaluate the program for two target groups in Labuhanbatu. In the contrary to the objective of the program, it is indicated that quite a large portion of the fund (35.78%) was not used for empowering the smalls scales shops/stalls. The recipients from the poor people category was constitute only 19.18% of the total number, who gets about 10.97% of the total fund allocated. Using two scenarios for sensitivity analysis and 12 % per year for discounting, this research conclude that the PDM-DKE program is beneficial but the benefit was enjoyed more by no-low-income recipients. However, there might possibilities that the program create some non-quantifiable benefit. The following recommendation are put forward: 1) To ensure that the use of aid and the determination of the terget group are accordance with the original objective, there is a need for monitoring, supervision and guidance at every stage of the implementation up to the lowest level. 2) Allocation of the aid should be more selective in order to avoid deviations in the implementation. 3) Further research is necessary to investigate the implementation of the program in wider scope